Implementasi Fuzzy-Mamdani untuk Pengendalian Suhu dan Kekeruhan Air Aquascape Berbasis IoT - Natanael Salim, Axel; Rahman, Abdul (Algoritme Jurnal Mahasiswa Teknik Informatika, 2022)
Aquascape consists of complex elements, hardscape, and softscape. Aquascape requires regular maintenance, one of which is maintaining the water quality so that the plants and living things in it can thrive and the aquascape remains pleasing to the eye. We can maintain water quality by maintaining the turbidity level and water temperature. By maintaining the turbidity of the water temperature, plants and living things in the aquascape will continue to thrive. To keep the water conditions clear and healthy, a system is needed to control the turbidity level and temperature of the aquascape water. This study builds a system that can maintain water quality in an Internet of Things-based aquascape by implementing the Fuzzy Mamdani algorithm to optimize a system that can adjust the fan speed to lower the water temperature and determine how long the water pump will run and flow. Water in the aquascape. The results of the tool test are obtained; if the temperature, pH, and water turbidity sensor values ​​are close to the normal water limits, the water pump will turn on. If the temperature is above 27.89ºC and the pH is above 13, the fan will run at full speed. To measure the accuracy of this aquascape system, MAPE is used with an error value of 3% for the fan data generated.